Investigation of protective effect of ellagic acid in phthalates-induced reproductive damage - Turkmen, Nese Basak; Ayhan, Idris; Taslidere, Asli; Aydin, Muhterem; Ciftci, Osman (Taylor & Francis Ltd, 2022)
Phthalates that people are exposed to every day are toxic carcinogenic chemicals with proven harmful effects on growth and reproduction. Ellagic acid (EA) is a polyphenol derivative known for its antioxidant properties. We hypothesized that the possible reproductive damage mechanism of phthalates is oxidative attack and ellagic acid could have a protective effect against radical forms in the body through its antioxidant properties. Thirty-two male rats were randomly divided into 4 groups, with 8 rats in each. Phthalate (DBP) was administered intraperitoneally and EA acid through gastric oral gavage (phthalate group 500 mg/kg/day DBP; EA group 2 mg/kg/day ellagic acid; the treatment group 500 mg/kg/day DBP and 2 mg/kg/day EA). The vehicle of DBP and EA, carboxymethyl cellulose was administered to control group. At the end of 4 weeks the testis tissue samples were taken under mild anesthesia. Tissue malondialdehyde, antioxidant parameters, sperm motility, sperm density and abnormal spermatozoon ratios were determined. Analysis was performed with One Way ANOVA test using SPSS 12.0 program. As a result; it has been shown that DBP causes oxidative damage by increasing the malondialdehyde level and decreasing antioxidant parameters, increased abnormal sperm rate and decreased sperm motility and concentration and histopathological damage so this damage is inhibited by the antioxidant activity of ellagic acid.
Keywords: Ellagic acid; antioxidant; phthalate; DBP; reproductive damage